POLITENESS STRATEGIES USED BY DEBATERS IN INTELLIGENCE SQUARED U.S DEBATE PROGRAM - PERMATASARI, RIZKY APRELLA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Politeness, Face, Face Threatening Act (FTA), Politeness Strategies, DebateLanguage is a tool for people to get and share information with others. When people get in interaction there are some different opinions between them. Sometimes these differences can cause a conflict in interaction if they do not payattention to their utterance and their interlocutor. Therefore people need politenessstrategy in the interaction. Politeness strategy is developed in order to minimize aconflict in interaction. The writer conducts a study about Politeness Strategies which shows the phenomena of politeness occuring in the debate program. Thereare two problems of the study that are proposed by the writer: (1) what FaceThreatening Act are performed by debaters in Intelligence Squared U.S debate program; (2) what types of politeness strategies are used by the debaters inminimizing threats in Intelligence Squared U.S debate program.This study used qualitative approach to describe the phenomena that  were studied clearly and systematically. Document analysis was also applied in  this study since the study analyzed the data from the transcript of utterances that were performed by debaters.This study showed that there were 16 utterances from the debaters that contain Face Threatening Act and Politeness Strategies. They threatened both positive and negative face but positive face was more threatened than negativeface. Disagreement, criticism, bringing of bad news, contradiction and challenge were the acts that threatened the other debaters’ positive face while suggestion and reminding were the acts that threatened the other debaters’ negative face. They also applied some of politeness strategies to redress their Face Threatening Act including 6 positive politeness, 4 negative politeness, 1 off record and 5 mix politeness strategies.The writer suggests the readers who conduct similar study to analyze theuse of Face Threatening Acts and Politeness Strategies such as the reason whysuch strategy is applied in other media like talk show program, movie, oradvertisement.